Gambaran Kejadian Abortus Inkomplit di Rumah Sakit Umum Daerah Wangaya Kota Denpasar - Ni Kadek Teja Anggrayani; Ni Wayan Manik Parwati; Ni Putu Riza Kurnia Indriana (Malahayati Nursing Journal, 2023)
ABSTRACT Incomplete abortion is an obstetric emergency that requires immediate treatment. Incomplete abortion is one of the contributors to maternal mortality. Risk factors for incomplete abortion include maternal characteristics, obstetric status, health status, nutritional status, and lifestyle. To determine the incidence of incomplete abortion cases at Wangaya Regional General Hospital, Denpasar City. This research is a description type using cross sectional. The research was conducted on August 12 - November 5, 2022. The population in this study were all pregnant women who experienced incomplete abortion in 2019-2021 at Wangaya Regional General Hospital, Denpasar City with a total of 425 people. Sampling was done with purposive sampling technique. The sample size in this study was 208 respondents. Data using secondary data collected using a check list sheet Type of secondary data. Data collection with a check list sheet. The research data were analyzed univariately. The highest incidence of incomplete abortion is in the age range of 20-35 years, secondary level education, private employees, multigravida, first trimester, child spacing is more or equal than 2 years, has no history of abortion, has no history of disease, normal nutritional status, and does not have a lifestyle that is detrimental to health. Pregnant women of productive age, multigravida, and first trimester are routine in doing antenatal care and do USC at least once in early pregnancy. Working mothers are advised to take adequate rest. Future research is expected to use primary data.  Keywords: Description, Incomplete Abortion  ABSTRAK Abortus inkomplit adalah suatu kegawatdaruratan dalam kebidanan yang memerlukan penanganan segera. Abortus inkomplit merupakan salah satu penyumbang terjadinya angka kematian ibu. Faktor risiko abortus inkomplit meliputi karakteristik ibu, status obstetri, status kesehatan, status gizi, dan pola hidup. Mengetahui gambaran kejadian kasus abortus inkomplit di Rumah Sakit Umum Daerah Wangaya Kota Denpasar. Penelitian ini berjenis deskripsi dengan menggunakan cross sectional. Penelitian dilakukan pada tanggal 12 Agustus - 5 Nopember 2022. Populasi pada penelitian ini adalah semua ibu hamil yang mengalami abortus inkomplit tahun  2019-2021 di Rumah Sakit Umum Daerah Wangaya Kota Denpasar dengan jumlah 425 orang. Pengambilan sampel dilakukan dengan teknik purposive sampling. Besarnya sampel pada penilitian ini  208 responden. Data menggunakan data sekunder yang dikumpulkan menggunakan lembar check list Jenis data sekunder. Pengumpulan data dengan lembar chek list. Data penelitian dianalisis secara univariat. Kejadian abortus inkomplit terbanyak berada pada rentang umur 20-35 tahun, pendidikan tingkat menengah, karyawan swasta, multigravida, trimester satu, jarak anak lebih atau sama dari 2 tahun, tidak memiliki riwayat abortus, tidak memiliki riwayat penyakit, status gizi normal, dan tidak memiliki pola hidup yang merugikan kesehatan. Ibu hamil usia produktif, multigravida, dan trimester 1 rutin dalam melakukan antenatal care dan melakukan USC minimal satu kali di awal kehamilan. Pada ibu yang bekerja disarankan untuk dapat melakukan istirahat yang cukup. Penelitian berikutnya diharapkan dapat menggunakan data primer. Kata Kunci: Gambaran, Abortus Inkomplit